Toward an understanding of health services use in women with binge eating disorder. - Striegel-Moore, R; Dohm, F; Wilfley, D; Pike, K; Bray, N; Kraemer, H; Fairburn, C (2004)
OBJECTIVE: This study examined health services use in community samples of 102 white and 60 black women with binge eating disorder (BED), 164 white and 85 black healthy comparison women, and 86 white and 21 black women with a noneating Axis I psychiatric disorder. RESEARCH METHODS AND PROCEDURES: Participants were matched on age, ethnicity, and education and were asked about their use of emergency room visits, outpatient physician visits for medical care, outpatient psychotherapy visits, and days spent in the hospital over the previous 12 months. Total health services use was computed. RESULTS: There were no between-group differences in outpatient physician visits or inpatient hospital days. Relative to healthy comparison women, women with BED and women with other Axis I disorders had increased total health services use, psychotherapy visits, and emergency department visits. Relative to women with noneating Axis I disorders, women with BED had less use of psychotherapy visits. Although obese white women were more likely to report emergency department visits than obese black women were, nonobese white women were less likely to report emergency department visits than nonobese black women were. DISCUSSION: That health services use by women with BED compared more with that of women with other Axis I disorders than with that of healthy women suggested that BED has clinical significance and is not benign in terms of its impact on the health care system. It appeared, however, that despite the availability of effective treatments, few women with BED received psychotherapy.